ผลการสอนด้วยการสร้างแบบจําลองเป็นฐานที่มีต่อสมรรถนะการสร้าง แบบจําลองและผลสัมฤทธิ์ทางการเรียนเคมีของนักเรียนมัธยมศึกษาตอนปลาย - วรกมล ปล้องมาก (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The purposes of this research were to (1) compare students’ modeling competencies before and after learning through modelling-based learning and (2) study chemistry learning achievement after learning through modelling-based learning. The sample was forty-three of eleventh grade students in academic year 2018 from a large secondary school in Bangkok, Thailand. The design of this pre-experimental research was one group pretest-posttest design. The students’ modeling competencies was evaluated before and after the instruction, while students’ achievement in chemistry was only evaluated after the instruction. The research instruments were (1) the modeling competencies test and (2) chemistry learning achievement test on organic chemistry. The collected data were analyzed by mean, percentage mean, standard deviation, dependent t-test and Wilcoxon Signed Ranks test. The research findings were summarized as follows:1.The levels of the modeling competencies after the experiment higher than before experiment at a .05 level of significance 2.The mean score of chemistry learning achievement was 69.21 percent, moderate level.